Kanûnî’nin Son Seferini Konu Alan Bazı Tasvirlerdeki Sembolik Dil üzerine - (:unkn) unknown (Istanbul 29 Mayis University - ISAM, TDV Centre for Islamic Studies, 2018)
This study is an analysis of the symbolic language observed in a number of miniatures depicting various events from the last years of Suleyman the Magnificent’s reign (926-974/1520-1566) until the beginning of that of Selim II (974-982/1566-1574). I will focus especially on the “tree stump motif” seen in the miniature depicting the event of deploying Suleyman the Magnificent’s corpse, attributed to Nakkaş Osman (d. after 1001/1592), found in Feridun Ahmed Bey’s (d. 991/1583) Nüzhet-i esrârü’l-ahyâr der-ahbâr-ı Sefer-i Sigetvar (Pleasures of the Secrets of Auspicious Men from the News of the Szigetvár Campaign, 976/1569), and in the “senility” portrait of Suleyman the Magnificent attributed to Nigârî (d. 980/1572). The tree stump is recognized as a cult motif that heralds the genealogical continuity of religious and political authority. I will argue that in the above mentioned miniatures, it represents the continuity of the dynasty, and the transfer of dynastic power. The “tree stump motif” and the depictions of nature and of animals in these miniatures were selected to complement the theme depicted and added into the composition to enhance the narrative. There seems to be an obvious interaction among the painter, the poet and the author reflected in the document. © 2019 Osmanli Arastirmalari - Journal of Ottoman Studies. All rights reserved.
Keywords: Accession to the throne event; Allegory; Nakkaş Osman; Nigârî; Ottoman miniatures; Survival of the state; The Ottoman dynasty; Tree stump with shoot